Brain-penetrant PQR620 mTOR and PQR530 PI3K/mTOR inhibitor reduce huntingtin levels in cell models of HD. (1st January 2020) - Singer, Elisabeth; Walter, Carolin; Fabbro, Doriano; Rageot, Denise; Beaufils, Florent; Wymann, Matthias P.; Rischert, Nadine; Riess, Olaf; Hillmann, Petra; Nguyen, Huu Phuc
Abstract: One of the pathological hallmarks of Huntington disease (HD) is accumulation of the disease-causing mutant huntingtin (mHTT), which leads to the disruption of a variety of cellular functions, ultimately resulting in cell death. Induction of autophagy, for example by the inhibition of mechanistic target of rapamycin (mTOR) signaling, has been shown to reduce HTT levels and aggregates. While rapalogs like rapamycin allosterically inhibit the mTOR complex 1 (TORC1), ATP-competitive mTOR inhibitors suppress activities of TORC1 and TORC2 and have been shown to be more efficient in inducing autophagy and reducing protein levels and aggregates than rapalogs. The ability to cross the blood-brain barrier of first generation catalytic mTOR inhibitors has so far been limited, and therefore sufficient target coverage in the brain could not be reached. Two novel, brain penetrant compounds – the mTORC1/2 inhibitor PQR620, and the dual pan-phosphoinositide 3-kinase (PI3K) and mTORC1/2 kinase inhibitor PQR530 - were evaluated by assessing their potential to induce autophagy and reducing mHTT levels. For this purpose, expression levels of autophagic markers and well-defined mTOR targets were analyzed in ST Hdh cells and HEK293T cells and in mouse brains. Both compounds potently inhibited mTOR signaling in cell models as well as in mouse brain. As proof of principle, reduction of aggregates and levels of soluble mHTT were demonstrated upon treatment with both compounds. Originally developed for cancer treatment, these second generation mTORC1/2 and PI3K/mTOR inhibitors show brain penetrance and efficacy in cell models of HD, making them candidate molecules for further investigations in HD. Highlights: PI3K/mTORC and mTORC inhibitors reduce levels of soluble and aggregated huntingtin. Catalytic mTOR inhibition ameliorates protein aggregation in cellular models of HD. PQR530 and PQR620 cross the BBB and effectively inhibit mTOR signalling.